Fare spazio. Jacques Derrida e la decostruzione dell’architettura - Vitale, Francesco (Scenari, 2021)
In 1985 Bernard Tschumi invited Jacques Derrida to collaborate with Peter Eisenman on a project within the framework of the La Villette Park’s retraining. Jacques Derrida will look after architecture for almost a decade, publishing essays, attending conferences, giving interviews. We aims to account for this rendezvous, showing in it the reasons that have led Derrida to open a dialogue with architects and theorists. In particular, we shall account for the link between architecture and deconstruction with regard to the so-called “metaphysicis of Presence”.